Aetiology and Hearing Status of Children under 12 years in a School for Hearing Impaired (Bangladesh Journal of Otorhinolaryngology, 2020)
Objective: To assess degree, type and cause of hearing loss in children under 12 years of age in preschool for hearing impaired children.Methods: This cross sectional study was carried out in children of integrated preschool for hearing impaired children (IPSHIC) of SAHIC, Mohakhali, Dhaka, from September 2010 to March 2011. 50 deaf children were included with age 3-12 years and clinically detected hearing impairment. Data were collected by detailed history, clinical examination and audiometric findings and result were expressed in table form.Results: Most of the children presented with bilateral profound hearing loss and majority of patients presented with sensorineural type of hearing loss. Family history positive in 36% cases and consanguineous marriage were found in 34%.Commonest causes of deafness was infection.Conclusion: Early detection with universal neonatal screening should be practiced in our country and early rehabilitation reveals better out come.Bangladesh J Otorhinolaryngol; April 2016; 22(1): 36-39